Study on the application of King’s combined uterine suture for hemostasis during cesarean section - Li Xia (BMC, 2021)
Abstract Introduction Postpartum hemorrhage is a serious complication of childbirth and is still the leading cause of maternal death worldwide. Lower uterine segment hemorrhage during cesarean section is an important cause of postpartum hemorrhage. Our objective is to expore the efficacy and safety of King’s combined uterine suture for hemostasis during cesarean section. Methods We examined 48 cases: 16 cases of pernicious placenta previa (including one case of twins), 11 cases of central placenta previa (including one case of twins), 18 cases of uterine scarring (including two cases of twins), as well as one case of twin pregnancy, two cases of breech presentation, and one case of pulmonary hypertension. The “King’s combined uterine suture” method for hemostasis was used in patients with lower uterine segment hemorrhage during cesarean section. Results The results showed that all patients had successful hemostasis during surgery, and there were no cases of hysterectomy. Conclusion We have concluded that King’s combined uterine suture is a fast and safe hemostasis method for cesarean section that can effectively reduce blood loss and restore the normal shape of the lower uterine segment. Furthermore, this suture method can reduce postpartum hemorrhage and hysterectomy rate, as well as improve maternal prognosis.